2020
DOI: 10.1007/s11154-020-09556-7
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of aggressive pituitary tumors (and its challenges)

Abstract: Pituitary tumors are not rare if prevalence rates from autopsy or radiological series are considered; approximately 0.5% of all pituitary adenomas will come to medical attention. Less than 0.1% of these pituitary adenomas will become malignant, and probably around 0.5% of all detected adenomas will display an aggressive course. However, the exact incidence of both aggressive pituitary adenomas and pituitary carcinomas is unknown, as most data come from series with selected patients, such as surgically treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 30 publications
2
34
1
2
Order By: Relevance
“…Although grading of symptoms was not possible in our study, the results imply persisting mental health issues despite achieved biochemical remission. The findings in study IV support two previous cross-sectional studies in which increased prevalence of psychopathology and cognitive impairment was found after remission for 11 (range 1-32), and 13 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) years, respectively (90,91).…”
Section: Study IVsupporting
confidence: 88%
See 3 more Smart Citations
“…Although grading of symptoms was not possible in our study, the results imply persisting mental health issues despite achieved biochemical remission. The findings in study IV support two previous cross-sectional studies in which increased prevalence of psychopathology and cognitive impairment was found after remission for 11 (range 1-32), and 13 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) years, respectively (90,91).…”
Section: Study IVsupporting
confidence: 88%
“…In a study by Dorn et al (89), including 33 patients with Cushing's syndrome, significant psychopathology was present in two thirds at diagnosis, and decreased to 24% 12 months after remission. However, compared to controls, cross-sectional studies have shown increased psychopathology and cognitive impairment after longterm remission for 11 (range 1-32), and 13 (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) years respectively (90,91).…”
Section: Neuropsychiatric Comorbiditiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The 2017 WHO classification recognizes pituitary tumors as having a low or high probability of recurrence [ 1 ]. Of pituitary tumors requiring surgical treatment, 15% are “aggressive” [ 37 ] but only 0.1% to 0.2% of these progress to become true carcinomas, as defined by evidence of cerebrospinal and/or systemic metastases [ 45-49 ]. Histopathological and molecular markers are unable to identify the very rare tumors that exhibit aggressive growth or very rarely malignancy.…”
Section: Aggressive Pituitary Neoplasmsmentioning
confidence: 99%